Effect of Trigonella Foenum against Ethylene Diamine Tetra Acetic Acid induced Nephrotoxicity in Male Albino Rats - I Barakat, A; Radwan, EH (Journal of Zoological Research, 2020)
Background Nephrotoxicity is a complication due to the effect of some toxic chemicals on kidney. Current study planned to screen the effect of Trigonella foenumaqueous seeds extracts on EDTA induced nephrotoxicity. Trigonella foenum known for its various medicinal properties is also a natural antioxidant and a free radical scavenger with no documented evidence as a nephron-protective agent. Objective To investigate the protective effects of aqueous seed extracts of Trigonella foenum. Material and Methods The present study was used 40 male albino rats (Rattus albinus) with weight of (150 ± 10) g with divided into four groups: control gp; EDTA gp (95 mg/kg); Trigonella foenum gp (500 mg/kg) and EDTA + Trigonella f oenum gp by gastric tube daily for 4 weeks. Blood urea, creatinine, GFR, creatinine clearance, MDA and GPx analyses and microscopic examination of kidney were performed. Results In the present study, Blood samples were taken from all groups and concentration of serum urea, creatinine, GFR, Creatinine clearance, MDA and GPx were determined. Histopathological observations were observed in kidney tissue. Data were analyzed using analysis of variance (ANOVA). EDTA induced an increase in urea and creatinine as well as there was a decrease in the concentration of GFR and creatinine clearance. The level of MDA was increase while the concentration of GPx was decrease in the serum of EDTA group. The aqueous extracts of Trigonella seeds significantly prevented renal damage by normalizing increased levels of renal markers. The correction of oxidative stress biomarkers was consistent with amelioration of the histopathological changes induced by EDTA. Hence, it is suggested that ameliorative effect of aqueous extract of Trigonella foenumagainst EDTA induced nephrotoxicity. Conclusion The present data suggest that aqueous extract of Trigonella foenum exhibits reno-protective effect in EDTA induced renal damage.
Keywords: Trigonella foenum; Nephrotoxicity; EDTA.